1994
DOI: 10.1007/bf02536250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of linoleic acid and eicosapentaenoic acid incorporation into human breast cancer cells

Abstract: To gain some insight into the mechanisms involved in the opposing effects of linoleic acid (LA) and eicosapentaenoic acid (EPA) on the growth and invasiveness of MDA-MB-435 human breast cancer cells, the dynamics of the uptake by cells and the incorporation of [14C]LA and [14C]EPA into major lipid and phospholipid pools, as well as the effects of unlabeled EPA or LA on the uptake and distribution of [14C]LA or [14C]EPA, respectively, were examined. Cells were exposed to [14C]LA (1.28 micrograms/mL) or [14C]EPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…[1][2][3][4] The anticancer role of omega-3 fatty acids has also been substantiated with dietary studies using many types of animals (including humans) and numerous different cell lines, including breast cancer. 8,10,19,20 In the study reported here, we investigated the effects of long-chain polyunsaturated omega-3 fatty acids on breast cancer cells both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The anticancer role of omega-3 fatty acids has also been substantiated with dietary studies using many types of animals (including humans) and numerous different cell lines, including breast cancer. 8,10,19,20 In the study reported here, we investigated the effects of long-chain polyunsaturated omega-3 fatty acids on breast cancer cells both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, including our own, 5,[19][20][21][22][23][24] have linked fish oil to induction of apoptosis. We found that DHA activates sphingomyelinase (SMYase) activity in the plasma membrane of Jurkat leukemic cells, increasing ceramide levels.…”
mentioning
confidence: 99%
“…It has been shown that both -3 and -6 long-chain PUFA added exogenously to cells in culture become part of the membrane phospholipid pool (24,25). Accumulation of exogenously added PUFA occurs in the phospholipid component of the membranes during the first 8-16 h of exposure, after which there was little or no accumulation.…”
Section: Altering -6 Composition Of Membrane Phospholipids In Nih 3t3mentioning
confidence: 99%
“…The preponderence of reports coming from a vide variety of primarily cancer cell types [155][156][157][158][159] indicate that DHA induces apoptosis and it has been suggested that DHA's anticancer properties are not due directly to cytotoxicity, but rather to the fatty acid's ability to induce apoptosis [160][161][162]. Siddiqui et al [163] have recently reviewed the role of DHA in enhancing both the cytosol-linked and mitochondrial-linked apoptotic pathways.…”
Section: Dha: Affect On Cell Signaling and Apoptosismentioning
confidence: 99%